2022
DOI: 10.3748/wjg.v28.i44.6249
|View full text |Cite
|
Sign up to set email alerts
|

Development of Epstein-Barr virus-associated gastric cancer: Infection, inflammation, and oncogenesis

Abstract: Epstein-Barr virus (EBV)-associated gastric cancer (EBVaGC) cells originate from a single-cell clone infected with EBV. However, more than 95% of patients with gastric cancer have a history of Helicobacter pylori ( H. pylori ) infection, and H. pylori is a major causative agent of gastric cancer. Therefore, it has long been argued that H. pylori infection may affect the development of EBVaGC, a subtype of gastric cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Therefore, it remains unclear whether H. pylori infection is a cofactor for EBV-induced gastric carcinogenesis or whether H. pylori and EBV act independently in the development of GC. The possibilities are either that EBV infection participates in H. pylori -induced GC tumorigenesis, or that H. pylori infection accelerates EBV-initiated carcinogenesis[ 29 ].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Therefore, it remains unclear whether H. pylori infection is a cofactor for EBV-induced gastric carcinogenesis or whether H. pylori and EBV act independently in the development of GC. The possibilities are either that EBV infection participates in H. pylori -induced GC tumorigenesis, or that H. pylori infection accelerates EBV-initiated carcinogenesis[ 29 ].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…EBVaGC is identified as EBV-infected tumor cells by polymerase chain reaction analysis and in situ hybridization and characterized by lymphoepithelioma-like histology, unique clinical features, and relatively desirable prognosis compared to non-EBV-associated cases (EBVnGC) ( 11 ). EBVaGC is associated with Caucasian or Hispanic ethnicity, male gender, younger age, history of gastric surgery, and unhealthy lifestyles (such as smoking and consumption of salty foods) ( 12 15 ). Helicobacter pylori infection has long been considered a causative factor for GC.…”
Section: Ebv and Ebvagcmentioning
confidence: 99%
“…Studies have found that EBV-associated gastric cancer (EBVaGC) accounts for approximately 10% of gastric cancers worldwide and that EBV infection is positively associated with the risk of gastric cancer [ 4 , 5 ]. More than 95% of patients with gastric cancer are found to have a typical history of Helicobacter pylori ( H. pylori ) infection, and EBV infection can promote the development of gastric cancer caused by H. pylori infection [ 6 ]. A recent study found that when normal gastric epithelial cells are infected with EBV, the intracellular microenvironment undergoes significant changes thereby promoting GC [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morphologically, cells undergoing ferroptosis have intact cytosolic membranes, normal-sized nuclei, no chromatin condensation, dense mitochondria, and residual cristae. Biochemically, cells undergoing ferroptosis exhibit elevated Fe 2+ levels, increased ROS levels, inactivation or depletion of glutathione peroxidase 4 (GPX4), inhibition of cystine/glutamate transporter protein SLC7A11 (also xCT, system xc-), and accumulation of lipid metabolites [ 6 ]. The transcription factor nuclear factor erythroid 2-related factor 2 (NRF2) is a key member of endogenous antioxidant defense systems [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%